Shaping Cash Transfer Impacts Through 'Soft-Conditions': Evidence from Lesotho. (28th June 2018) - Pace, Noemi; Daidone, Silvio; Davis, Benjamin; Pellerano, Luca
Abstract: Cash transfer programmes have been shown to have positive effects on a variety of outcomes. While much of the literature focuses on the role of conditionality in achieving desired impact, this paper focuses on the role of 'soft conditionality' implemented through both 'labelling' and 'messaging' in evaluating the impact of the Child Grants Program in Lesotho, an unconditional cash transfer programme targeting poor households with orphans and vulnerable children. Beneficiary households received a clear message that the transfer should be spent on the interest and needs of children. Our findings suggest that 'soft conditionality' does play a role in increasing expenditure for children, especially on education, clothing and footwear. Results indicate in fact that transfer income is spent differently from general income as it exerts both an income and a substitution effect. This behavioural change is confirmed by comparing the ex-ante expected behaviours with the ex-post actual response to the programme. We find that for expenditure categories linked to the well-being of children the ex-post response was much higher than the ex-ante expected behaviour.